Turismo de observação de cetáceos na ilha de São Miguel (Açores) - Toste, Ana Margarida Pimentel (2024)
Dissertação de Mestrado em Biologia Marinha e Alterações Globais apresentada à Faculdade de Ciências e Tecnologia The location of the Azores, its accentuated bathymetry and the interaction with the dynamic oceanography of the area, favors the growth and aggregation of primary production, facilitating the occurrence of higher trophic levels, for example, top predators such as cetaceans. The regular presence of sperm whales in the waters of the archipelago was an attraction for American whalers, who arrived in the Azores in the 18th century, providing not only knowledge to the Azoreans about sperm whales, but also guaranteeing socioeconomic advancement in the area for a few centuries with the development of coastal and artisanal whaling that remained in the Region until 1987. After the transition from whaling to cetacean observation, in 1989 and the beginning of the 90s, cetaceans began to be recognized for their importance at a biological level, but also historically, socially and economic. With a view to responsible and respectful tourism, many whale watching companies have adapted a data recording system, such as the company Futurismo Azores Adventures, supporting information about the different species with recurring and long-term data collection. This report's main objectives are to study the biodiversity of cetaceans on the island of São Miguel (Azores) from July to September 2023, the temporal and spatial distribution of the species observed and to carry out the photo-identification of sei whales observed in 2022 and 2023, carried out with the company Futurismo Azores Adventures. The data used were collected during cetacean observation tours carried out on the south coast of São Miguel. During the internship period, 12 species of cetaceans and one family (Ziphiidae) were observed out of the 28 listed in the Azores: 3 belonging to the suborder Mysticeti and 10 (including the family) to the suborder Odontoceti, with beaked whales, in this work, all being considered species of the Ziphiidae family. The most ...